A study on scenario and assessment of health camps in north Karnataka by KLE’s Dr. Prabhakar Kore hospital: facilitate health care to community people - Koppad, Rajashree; Kudachi, Allamprabhu B.; M., Dayanand; Kunchanur, Mahantesh (International Journal Of Community Medicine And Public Health, 2024)
Background: Health-camps offering specific populations brief medical interventions could be helpful as 60% of India’s population lacks access to basic medical facilities. This study provides useful insights for organizing, planning, and implementing health-camps by epidemiologically analyzing a health-camp event in a rural area in southern India; arranging and planning health-camps, as well as using exit interviews to gauge participants’ expectations and levels of satisfaction; determine the health issues that impoverished residents of Belagavi district. Health-camp is a strategy for universal health coverage used by highly qualified doctors to offer the underprivileged affordable care. Methods: A self-structured questionnaire was utilized to interview 219 beneficiaries for the research. These were divided into sections containing participant sociodemographic data, 21 items that evaluate satisfaction of health camps and question concerning expectations of post camps. 4-point rating system was employed to collect the responses: poor (1) to excellent (4). Ages ≥14 for men or women. Along with medical or non-medical services, the questionnaire also included questions about camp site accessibility, reception counters, initial medical check-ups, screening tests, behavior of doctors and other staff, waiting times, drug supply, preliminary information, referrals, length of health camp, cleanliness, and camp performance overall. The participants’ average age was 40.2 years. Results: Both genders participated equally in study, 76% married and 46% participants studied up to high school. 59% of the participants, belong to a nuclear family, rural residence (81%), occupation 33% housewife and 26% business. More number of participants (46.51%) received information about camps through the village announcement. Conclusions: The health camp was conducted and appreciated by most of the participants and suggested to continue the same health camps programme to promote good health every one the area.